Rule of law and balance of power sustain US dollar preeminence - Seghezza, Elena (369 EGFR SIGNALING IMPAIRS THE ANTIVIRAL ACTIVITY OF INTERFERON-ALPHA, 2018)
In the last few decades, and especially since the financial crisis of 2007–2008, uncertainty about the future of the US dollar has been mounting. A broad-based theoretical debate on the decline of the dollar and its consequences has begun. There is a large body of studies that sees the origin of an international money as a market-led process. In this view, because the United States will very soon lose its economic pre-eminence the US dollar will consequently share its international role with other currencies or even be replaced by the renminbi. In this paper we contest this argument, focusing on the conditions that make a fiat money acceptable in international transactions. Trust in a type of money like this needs an institutional framework that guarantees the property rights of currency holders. This framework implies a high level of rule of law domestically and a high level of state capability in the international balance of power. Since at present no other currency fulfils these two requirements at the same time, the dominance of the US dollar as an international money is going to last.